Walking in both worlds: rethinking Indigenous knowledge in the academy. Issue 5 (4th May 2017) - Arnold, Josie
ABSTRACT: Six generations ago, my Celtic forebears came to Australia as convicts and invaders displacing Indigenous peoples. As a scholar today, I am interested in how Indigenous knowledge remains a challenge in Australian Universities even in this postmodern and postcolonial moment. This paper recognises the need to extend discussion about how Indigenous people might be facilitated within the academy to bring their knowledge models into the university and its traditional dominant knowledge systems. This paper looks at Practice-Led Research (PLR) as a way of supporting the transition of Indigenous community scholars into university postgraduate courses. It explores how PLR may contribute to an appropriate entry point into postgraduate studies for some Indigenous practitioner-candidates who have significant life experiences and narratives and/or productions of artefacts that act to replace the breadth of undergraduate credentials. Indigenous people are facilitated in bringing their knowledge models into the university and the academy when we act upon being inclusive rather than exclusive regarding the explication and definition of knowledge within the academy. In accepting and acting upon the concept that traditional forms of knowledge are extended by non-traditional Indigenous forms of knowledge, we also enrich the scholarly conversation about how alternative forms of knowledge can add dynamism to the academy.